PELATIHAN PENENTUAN NILAI ASET TETAP DAN METODE DEPRESIASI PADA SISWA SMAN 20 KABUPATEN TANGERANG - Kurniawati, Herni; Kim Lie, Irene; Ratna Sari, Vinetta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
This PKM targets students of SMA Negeri 20 Tangerang Regency so that they can better understand the science of accounting, especially those related to fixed assets owned by schools and businesses. School/company fixed assets are valued based on their actual condition (cost minus accumulated depreciation) and presented in the year-end financial statements. There are five methods of depreciation of fixed assets that you will learn in this training: the straight-line method, the Japanese year digit method, the double declining balance method, the man-hour method, and the production production method The data used in this PKM are primary data obtained directly from SMA Negeri 20 Kabupaten Tangerang, including data from interviews with principals and teachers. Meanwhile, secondary data was obtained from books, magazines, and the internet to support this research. The PKM was carried out successfully until it was completed on Friday, November 10, 2023 at 10.00 WIB. PKM is carried out through school visits with students. The mandatory output of PKM is made PKM journal and as an IPR as an additional output.